Periventricular Hemorrhage in Term and Late Preterm Neonates: Risk Factors and Outcomes - Ashraf Abou-Taleb; Hisham A. Alghany Algahlan (Mashhad University of Medical Sciences, 2019)
Background: Periventricular hemorrhage (PVH) is common in early preterm neonates but much less common in term and late preterm neonates. The aim of this study was to identify the risk factors and outcomes of PVH in term and late preterm neonates in a tertiary care center in Upper Egypt. Methods: A total of 33 term and late preterm (≥ 34 weeks of gestation) neonates (18 females and 15 males) admitted at the neonatal intensive care unit (NICU) of Sohag University Hospital and diagnosed with PVH from January 2016 to October 2018 were included in this prospective study. The neonates with major congenital malformation of the nervous system were excluded. The risk factors for PVH were ascertained, and the diagnosis was confirmed by transcranial ultrasound, computed tomography or magnetic resonance imaging. The outcomes were assessed at discharge time and the age of 6 months. Results: ThePVH was diagnosed in 5.9% of the neonates. The median of age was 12 days (age range: 2-28 days) at presentation, and convulsions were the most frequent presentations followed by poor suckling and pallor. The risk factors for PVH included prolonged prothrombin time, thrombocytopenia, non-administration of vitamin K, and prolonged labor in 54.5%, 30 %, 30 %, and 27.3% of the cases, respectively. Moreover, 26 (78.7 %) cases were discharged with good conditions, and 7 (21.2 %) subjects died in the NICU. The investigation of the patients' follow-up at the age of 6 months revealed neurological impairments in 36 % of the survivors. Grade IV and III PVH had mortality rates of 66.67% and 18.75%, respectively (P=0.009). Neurodevelopmental impairments were more frequent in Grade III and IV (P=0.002). Conclusion: The incidence of PVH was 5.9% among term and late preterm neonates admitted to our NICU. Coagulation disorders and prolonged labor were the leading risk factors. Most patients had favorable outcomes, and one-third of the cases had neurodevelopmental impairments. In addition, mortality was reported in one-fifth of the neonates. Severe grades of PVH had the worst outcomes.